Keputusan Pendanaan Kembali Obligasi: Tinjauan Literatur dan Implikasi Manajerial - Saharani Dewi Safitri; Siska Amelia Tafsilatul Mufsida; Madinatul Munawaroh; Melani Putri Dewitasari; M. Angga Maulana; Romi Damar Zaenal Ma'ruf (Journal of Management and Bussines (JOMB), 2025)
This study aims to examine the mechanisms, influencing factors, and implications of bond refinancing decisions in the context of corporate financial management, using a case study of PT Semen Indonesia (Persero) Tbk. The research method used is a literature review with a systematic and thematic approach, collecting and analyzing various empirical studies and secondary data from reputable journals between 2010 and 2025. The results indicate that bond refinancing decisions are influenced by financial factors, regulations, industry characteristics, and managerial aspects, and impact interest expense reduction, capital structure improvement, and company performance. This is evidenced by PT Semen Indonesia's success in reducing annual interest expense by Rp 69 billion through bond refinancing. In conclusion, bond refinancing is an effective financial strategy for improving capital efficiency and company profitability if implemented with careful planning and supported by conducive market conditions.   Keywords: Bond Refinancing, Capital Structure, Interest Expense, Financial Management